Structural Characterization of Bacillus subtilis Membrane Protein Bmr: An In Silico Approach - Nargotra, Amit; Rukmankesh; Ali, Shakir; Koul, Surrinder (Current Computer - Aided Drug Design, 2014)
Efflux pump - a membrane protein belonging to Major Facilitator (MF) family and associated with Multi Drug Resistance (MDR) has been a major factor in drug resistance of bacteria. In the era when no new effective antibiotic had been reported for years, the detailed study of these membrane proteins became imperative in order to improve the efficacy of existing drugs. The Bacillus subtilis membrane protein Bmr belongs to the super family of major facilitator proteins and is one of the first-discovered bacterial multidrug-efflux transporters. Development of Bmr inhibitors (B. subtilis) for least resistance, better drug sustainability and effective cellular activity requires three dimensional structure of this protein which has not yet been determined. In this communication structural characterization of this important efflux pump has been attempted using in silico approaches. The modeled structure of Bmr has been found to have 12 main helical segments interspersed by loops of variable lengths at regular intervals with both N- and C-termini on the same side of membrane. Docking of the known inhibitor reserpine on to the predicted structure of Bmr and its mutants signified the importance of the residues Phe143, Val286 and Phe306 in the interaction with the ligand. Besides this, the role of Arg313 and Phe309 in the H-bond formation and π-π interaction respectively, with reserpine was the new significant finding based on the interaction studies. The structure elucidation of Bmr and the role of these residues in binding to the ligand are expected to have a great impact on the efflux pump inhibition studies around the world and hence in the efficiency of the existing antibiotic drugs.
Keywords: Bmr